Experimental Study of a Radial Turbine Using Pitch-Controlled Guide Vanes for Wave Power Conversion (International Journal of Rotating Machinery)
In order to develop a high-performance radial turbine for wave power conversion, a radial turbine with pitch-controlled guide vanes has been proposed and manufactured in the study. The proposed radial turbine has been investigated experimentally by model testing under steady and sinusoidal flow conditions. Then, the experimental results have been compared with those of the conventional radial turbine for wave power conversion, that is, a radial turbine with fixed guide vanes. As a result, the running characteristics of the proposed radial turbine under steady and sinusoidal flow conditions were clarified and the effect of diffuser setting angle of guide vane on the turbine characteristics was presented. Furthermore, it seems that the proposed radial turbine is much superior to the conventional radial turbine.